Low spring primary production and microplankton carbon biomass in Sub-Antarctic Patagonian channels and fjords (50–53°S) - Jose Luis Iriarte; Luis Antonio Cuevas; Fernanda Cornejo; Nelson Silva; Humberto E. González; Leonardo Castro; Paulina Montero; Cristian A. Vargas; Giovanni Daneri (Arctic, Antarctic, and Alpine Research, 2018)
It is relevant to understand the processes and factors that modulate the efficiency of the carbon pump throughout the ecosystem of Patagonian fjords. Spatial variability of primary productivity and bacteria-microplankton biomass was assessed in relation to inorganic nutrients and stratification across nearshore zones of southern Patagonia (50–53°S) in austral spring 2009. Estimates of primary productivity (300–500 mg C m−2 d−1) and phytoplankton biomass (9–180 mg chlorophyll-a m−2) were low at offshore and inshore waters. Synergistic effects of low silicic acid concentrations and poor light penetration because of salinity-driven stratification of glacier meltwater in springtime appeared to negatively affect phytoplankton carbon biomass and primary production in this sub-Antarctic region. The knowledge of the relative importance of nutrient sources and light is especially significant for Patagonian glacier-fjord systems that are expected to receive higher freshwater inputs and will be more stratified in the future.